Apolipoprotein E genotype and the relationship between chitinase 3‐like protein 1 and postoperative delirium: Potential gene‐protein interactions: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Vasunilashorn, Sarinnapha M.; Inouye, Sharon K.; Ngo, Long H.; Fong, Tamara G.; Jones, Richard N.; Dillon, Simon T.; Libermann, Towia A.; O'Connor, Margaret; Arnold, Steven E.; Xie, Zhongcong; Marcantonio, Edward R.
Abstract: Background: Delirium and Alzheimer's disease (AD) are common causes of late‐life cognitive impairment with clear epidemiologic links; however, the pathophysiology underlying these links remains unclear. Our recent work suggests that Apolipoprotein E (APOE) ɛ4, the strongest genetic risk marker for AD, does not confer significantly increased risk of delirium in older surgical patients. However, APOE ɛ4 status did modify the relationship of C‐reactive protein (CRP) with delirium, with increased risk for delirium in ɛ4 carriers with high levels of CRP. We now examine whether APOE genotype modifies the established association between inflammatory marker chitinase‐3‐like protein‐1 (CHI3LI/YKL‐40) and postoperative delirium. Methods: We examined patients without dementia age≥70 undergoing major non‐cardiac surgery in the SAGES: Successful AGing after Elective Surgery study. We collected blood, extracted DNA, and performed APOE genotyping using allele specific polymerase chain reaction assays, considering APOE ɛ4 vs. non‐ɛ4 carriers. Plasma YKL‐40, measured on postoperative day 2 (POD2) by ELISA, was examined using sample‐based quartiles (Q1‐Q4). Delirium status was determined with daily interviews rating the Confusion Assessment Method, augmented by a validated chart review. We used generalized linear models adjusted for age, sex, surgery type, and stratified by APOE ɛ4 carrier status, to determine whether APOE modifies the association between YKL‐40 and delirium. Results: Among the 557 patients (mean age 76.7 [standard deviation 5.2], 58% female, 81% orthopedic), 19% were APOE ɛ4 carriers. Postoperative delirium occurred in 24%. The YKL‐40‐delirium relationship differed by APOE status. Among APOE non‐ɛ4 carriers, we found a significant relationship between YKL‐40 and delirium (relative risk [RR] (95% confidence interval [CI] for YKL‐40 Q4 vs. Q1: 2.6(1.4‐4.9) and Q3 vs. Q1: 2.3(1.2‐4.5); p‐trend<.01). Among APOE ɛ4 carriers, YKL‐40 was not significantly associated with delirium (RR(95% CI) for YKL‐40 Q4 vs. Q1: 2.0(0.6‐6.6) and Q3 vs. Q1:1.1(0.3‐3.5); p‐trend = 0.37). Conclusions: APOE non‐ɛ4 carriers may have increased risk of delirium conferred by post‐surgical inflammation specific to the type 2 immune response (high POD2 YKL‐40). These results differ from our prior results with CRP, and raise the intriguing possibility that differing APOE genotypes may interact at different points in the inflammatory pathway leading to delirium.